Cognição Numérica em Crianças com Transtornos Específicos de Aprendizagem - Da Silva, Paulo Adilson [UNESP]; Ribeiro, Fabiana Silva; Santos, Flávia Heloísa [UNESP] (Associacao Brasileira de Psicologia, 2015)
The aim of this study was to investigate the development of specific domains of Numerical Cognition (Number Sense - NS, Number Comprehension - NC, Number Production - NP, and Calculation - CA) in Brazilian children with Specific Learning Disorders. The study included 72 children (36 boys), from 9- to 10-years-old, enrolled in 4th and 5th years of elementary school of public schools at countryside of Sao Paulo State, Brazil. They were divided into three groups: control (CT, N = 42), Developmental Dyslexia (DL, N = 11) and Developmental Dyscalculia combined with dyslexia (DDc, N = 19). All participants had intellectual level within the normal range, however, children from the last two groups had Learning Disorders classified by School Achievement Test - TDE (Stein, 1994) and DDc children received necessarily classification as 'inferior' in Arithmetic Test of TDE. The children did not differ in NS. DL and DDc children showed slight deficits in NC. However, DDc children had moderate in NP and mild to moderate deficits in CA, which indicates a more generalized impairment in Numerical Cognition. Furthermore, DDc children showed discrepancy in Numerical Cognition performance when compared to the other groups. Thus, children with Learning Disorders showed different performances in Numerical Cognition, although both groups had preserved SN, DDc children showed higher deficits and discrepancy in relation DL and typically developing children.
Numerical cognition in children with specific learning disabilities
Keywords: Children; Developmental Dyscalculia; Developmental Dyslexia; Numerical Cognition; Specific learning disabilities